Immunohistochemical characteristics of MMP-9 and TIMP-1 markers expression in the cerebral cortex in diabetes mellitus type 2 - V. O. Shavrin (Zaporožskij Medicinskij Žurnal, 2020)
Aim – to study the features of immunohistochemical expression of MMP-9, TIMP-1, MMP/TIMP ratio in the cerebral cortex in diabetes mellitus type 2.